Dietary Trace Minerals - Tako, Elad (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Dietary trace minerals are pivotal and hold a key role in numerous metabolic processes. Trace mineral deficiencies (except for iodine, iron, and zinc) do not often develop spontaneously in adults on ordinary diets; infants are more vulnerable because their growth is rapid and their intake varies. Trace mineral imbalances can result from hereditary disorders (e.g., hemochromatosis, Wilson disease), kidney dialysis, parenteral nutrition, restrictive diets prescribed for people with inborn errors of metabolism, or various popular diet plans. The Special Issue "Dietary Trace Minerals" comprised 13 peer-reviewed papers on the most recent evidence regarding the dietary intake of trace minerals, as well as their effect on the prevention and treatment of non-communicable diseases. Original contributions and literature reviews further demonstrated the crucial and central part that dietary trace minerals play in human health and development. This editorial provides a brief and concise overview of the content of the Dietary Trace Minerals Special Issue.